Sonodynamic Therapy: A Potential Technique for Cancer Treatment - Kushwaha R.; Banerjee S. (My University, 2025)
Cancer remains a frontier health challenge for humankind, both socially and economically. Despite significant advances in cancer therapies, the problem of drug resistance and side effects of current clinical cancer therapies drives the relentless pursuit of advanced therapeutic modalities. In this regard, ‘Sonodynamic Therapy’ (SDT) has emerged as a promising non-invasive cancer treatment modality, combining sonosensitizers (SSs) with focused ultrasound waves to selectively kill cancer cells. In this article, we discuss the advancements in SDT using organic compounds, nanomaterials, and transition metal complexes as sonosensitizers. The use of organic compounds/nanoparticles enhances the precision and efficacy of SDT, while transition metal complexes offer robust properties and imaging capabilities. Moreover, SDT showed promising feasibility and safety under the clinical trials, showing significant tumour size decrease and even complete removal in some cases. Beyond cancer, SDT also presented significant results for treating bacterial infections and neurological disorders. Overall, SDT represents a substantial advancement in cancer treatment, offering a targeted, non-invasive approach with the potential for multimodal therapy. It has all the potential to be one of the beneficial and safer next-generation cancer therapies. © Indian Academy of Sciences 2025.